A Poet for All Seasons - Hugo, Daniel (Werkwinkel, 2014)
This is a translation of a general introduction to an anthology of poetry by Olga Kirsch. Major themes and motifs of her work are outlined, as well as a short biography of the authoress is presented. The selection from the poems of Olga Kirsch was published to celebrate her 70th birthday on 23rd of September 1994 as Nou spreek ek weer bekendes aan: ’n Keur 1944-1983 [Now I’m Again Addressing Familiar Ones: A Selection 1944-1983]. For the purposes of the translation the ending of the original introduction has been altered.